Researches of the neutralizing antibody distributions and antibody titers against parainfluenza 3 (pi-3) virus in cattle in livestock central research institute of konya - Feridun Öztürk; Asuman Toker; Sibel Yavru; Yılmaz Gökçay (Eurasian Journal of Veterinary Sciences)
In this study the blood sera collected from 238 cattle belonging to Livestock Central Research Institute of Konya were examined by micro-neutralisation test against parainfluenza-?) (PI-3) virus from the point of neutralizing antibodies. 116 cattle blood sera (49.57%) in a 1:5 dilution were found to be positive against PI-3 virus. It was determined that the antibody titers of positive sera ranged 1:5.63-1:317.